Advantages of technetium pyrophosphate scintigraphy over plasma enzyme analysis in estimation of anterior myocardial infarct size. Issue 2 (February 1981) - Saltissi, S; Robinson, P S; Webb-Peploe, M M; Coltart, D J; Croft, D N
Abstract : Infarct size was estimated by cumulative creatine kinase MB isoenzyme (CKMB-r) release and by technetium 99m stannous pyrophosphate (TcPYP) scintigraphy in 27 patients with acute anterior myocardial infarction. In eight patients, scintigraphy showed a central area of reduced tracer uptake surrounded by a peripheral rim of increased TcPYP accumulation ("doughnut" pattern). This appearance occurred only in large infarcts and the maximal scintigraphic area (51.3 +/- 2.8 cm2, mean +/- SEM) in this group was significantly greater than that in the remainder (28.1 +/- 2.5 cm2). Correlation between CKMB-r and maximal scintigraphic infarct area was moderate in the whole group. Exclusion of patients, however, with "doughnut" scintigrams in which correlation was very poor, resulted in substantial improvement in the remainder. It is suggested that in the central regions of large "doughnut" infarcts, reduced blood flow hinders the efflux of CKMB from the centre causing an underestimate of infarct size. Pyrophosphate scintigraphy appears to be more accurate than CKMB release in measuring the size of these large anterior infarcts.